2014
DOI: 10.1186/1472-6874-14-110
|View full text |Cite
|
Sign up to set email alerts
|

Molecular breast cancer subtypes and therapies in a public hospital of Northeastern Brazil

Abstract: BackgroundThe frequencies of molecular breast cancer subtypes vary among different human populations. The Northeastern region of Brazil has a mixed population of African, Indigenous and European ancestry. This retrospective study investigated breast cancer subtypes and applied therapies in a public hospital of Northeastern Brazil.MethodsData of 633 patients with invasive breast cancer from 2005 to 2011 were obtained from medical records. Status of hormone receptor (HR), HER2 and Ki67 expression index of 269 ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
(80 reference statements)
4
14
0
4
Order By: Relevance
“…The immunostaining results of ER, PR and Her-2/neu in this study are in agreement with similar recent studies (Andrade et al, 2014;Elesawy et al, 2014). However a variable difference does exist with others (Bhargava et al, 2009;Cheang et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The immunostaining results of ER, PR and Her-2/neu in this study are in agreement with similar recent studies (Andrade et al, 2014;Elesawy et al, 2014). However a variable difference does exist with others (Bhargava et al, 2009;Cheang et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…We found triple negative more common in younger age group in keeping with studies from Netherland (Kruijf et al, 2014). In contrast a study from Brazil found significantly increased rates of triple negative tumors, in patients above 50 years age (Andrade et al, 2014). Thus there are wide variations from different regions and populations with regards to the prevalence of the molecular subtypes, probably due to genetic reasons or methodology of studies and calculation.…”
Section: Discussionsupporting
confidence: 86%
“…Genetic studies associated with studies on the clinical progression of breast cancer have shown that prognosis is better with the luminal A subtype compared to the other subtypes . According to the usual immunohistochemical classification, this subtype accounts for around 60% of cases of breast carcinoma , a proportion that is similar to that found in the present sample (58.1%). With the usual immunohistochemical classification model, luminal A tumors are defined as those that are positive for the hormone receptors (estrogen and/or progesterone receptor‐positive) and negative for HER2 overexpression.…”
Section: Discussionsupporting
confidence: 65%
“…16 Likewise, a group from the Northeast region of Brazil reported that nearly 50% of 633 patients with invasive breast cancer had HER-2-positive tumors by IHC. 17 The relevance of these findings is still unclear, and whether they represent underlying biological phenomena or simply the play of chance remains to be investigated. The lower number of samples from the North and Midwest regions as compared with the other three regions is one limitation of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, only a few studies have been conducted in Brazil, most of which relatively small in size or retrospective in nature. [16][17][18] In the current study, we prospectively attempted to investigate the frequency of HER-2-positive breast cancer in a large sample of Brazilian women, along with the standardization of preanalytic procedures used in the assessment of HER-2 and the association between HER-2 status and various tumor and patient features, including geographic location.…”
Section: Introductionmentioning
confidence: 99%